Profile of Obstetric and Iatrogenic Fistula Surgeries at Kathmandu Model Hospital - Shrestha, Ranjana; Karki, Aruna; Dangal, Ganesh; Pradhan, Hema; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Vesico-vaginal fistula (VVF) is an abnormal fistulous communication between the bladder and/or urethra and the vagina that allows continuous involuntary discharge of urine into the vaginal vault affecting patients’ medical, physical, mental, social and sexual life. The aim of this study was to review and deliver a profile, their demography and outcome in the early phase of fistula surgery performed in our institute. Methods: This was a retrospective study of 222 patients who underwent fistula surgery during the period of January 2012 to March 2018 in Kathmandu Model Hospital. The fistula were classified according to Goh`s system. Patients’ demography, obstetric characteristics and fistula repair outcomes were reviewed. The primary outcome was in terms of urinary continence. Results: A total of 222 women aged between 10 to 65 years with a mean age of 31.4 were included. Majority of the patients had fistula due to obstetrical cause, contributing 58% (n=127) and in 42 % (n=95) of patients had fistula of gynecological etiology. Most of the patients had fistula of type 1a, contributing 38% (n=84) and only 0.01% (n=3) of type 3c and 4b according to Goh’s classification. Among 127 fistulas repaired of obstetric etiology100 (78.7%) patients and 85 (89.4%) out of 95 fistula patients of gynecological cause were continent and dry. Conclusions: Our study showed obstructed and prolonged labor was the major cause of obstetric fistula, however iatrogenic fistula was also becoming common. Majority of our cases had successful outcome with some degree of stress in some patients.